2012
DOI: 10.1038/onc.2012.237
|View full text |Cite
|
Sign up to set email alerts
|

Terminal differentiation and loss of tumorigenicity of human cancers via pluripotency-based reprogramming

Abstract: Pluripotent cells can be derived from various types of somatic cells by nuclear reprogramming using defined transcription factors. It is however unclear whether human cancer cells can be similarly reprogrammed and subsequently terminally differentiated with abrogation of tumorigenicity. Here, using sarcomas we show that human derived complex karyotype solid tumors: (1) can be reprogrammed into a pluripotent-like state as defined by all in vitro criteria used to define pluripotent stem cells generated from soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
135
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(138 citation statements)
references
References 58 publications
(90 reference statements)
1
135
0
2
Order By: Relevance
“…Recent progress has demonstrated that P53 mutations can enhance the efficiency of reprogramming, and upregulation of KLF4 in mutant somatic cells, or P53-knockout cells, produces aggressive cancers in mice (Sarig et al, 2010). Reprogramming of cancer cells by pluripotency factors has been proposed as potential cancer therapies due to their capability to restore terminal differentiation of cancer cells in vitro, increase the responsiveness of cancer cells to chemotherapy in vitro, and reduce the tumorigenicity in vivo (Zhang et al, 2013).…”
Section: Role Of Klf4 In Cscsmentioning
confidence: 99%
“…Recent progress has demonstrated that P53 mutations can enhance the efficiency of reprogramming, and upregulation of KLF4 in mutant somatic cells, or P53-knockout cells, produces aggressive cancers in mice (Sarig et al, 2010). Reprogramming of cancer cells by pluripotency factors has been proposed as potential cancer therapies due to their capability to restore terminal differentiation of cancer cells in vitro, increase the responsiveness of cancer cells to chemotherapy in vitro, and reduce the tumorigenicity in vivo (Zhang et al, 2013).…”
Section: Role Of Klf4 In Cscsmentioning
confidence: 99%
“…These findings support the notion that the epigenetic modification of a cancer cell via nuclear reprogramming could correct some malignant effects of oncogene activation and oncosuppressor gene inactivation, which may constitute the basis for a novel strategy to control tumor progression. 81,82 Zhang et al 81 reported the terminal differentiation and loss of tumorigenicity of human sarcomas via pluripotency-based reprogramming, but these authors failed to observe benign mature tissue elements in their teratomas assays. Kim et al, 83 the only group that has reported the successful generation of a patient-derived iPS cell line from human pancreatic ductal adenocarcinoma (PDAC), only obtained one iPS-like line from a pancreatic cancer harboring a KRAS mutation, the predominant driver of PDAC, and a deletion in exon 2 of the pivotal tumor suppressor CDKN2A.…”
Section: Precrime-ips Mouse Avatars Generation and Utilitiesmentioning
confidence: 99%
“…However, these authors reported only xenograft formation with no histology or immunohistochemistry. Zhang et al 81 recently demonstrated that the reprogramming of sarcoma cells using the 4 canonical Yamanaka genes plus Nanog and Lin28 created cancer cells that lost their tumorigenicity, exhibited reduced drug resistance, and dedifferentiated as iPS cells into various lineages, such as fibroblasts and hematopoietic lineages. Interestingly, the expression of endogenous c-Myc appeared to be reduced in their cellular model, and it was hypermethylated during the reprogramming process.…”
Section: Precrime-ips Mouse Avatars Generation and Utilitiesmentioning
confidence: 99%
“…This paper presents an alternative approach to cancer cell reprogramming towards a differentiated state, by skipping the iPSCs production passage usually found in the literature [9]. We supposed that cancer cells already showed sufficient stem-cell-like behavior to be ready for direct differentiation towards other germ layer lineages.…”
Section: Commentarymentioning
confidence: 99%
“…This metabolic switch is evidenced by a modulation in the expression of glycolysis enzymes, with a lowered expression of the glycolytic enzyme isoforms involved in the Warburg effect such as HK2, IDH2 and PKM2 [7] Concomitantly, we observe an increase in oxidative phosphorylation, as deduced by the decreased ATP content in differentiated cells compared to SH-SY5Y cells, following the in vitro inhibition of the mitochondrial electron transport chain. Restoration of mitochondrial activity is accompanied by a marked increase in Sirt3 activity [8].This paper presents an alternative approach to cancer cell reprogramming towards a differentiated state, by skipping the iPSCs production passage usually found in the literature [9]. We supposed that cancer cells already showed sufficient stem-cell-like behavior to be ready for direct differentiation towards other germ layer lineages.…”
mentioning
confidence: 99%